Prosocial Behavior of Elementary School Students Based on Gender Differences in Society 5.0 - Muhammad Misbahudholam AR; Framz Hardiansyah (Journal of Innovation in Educational and Cultural Research, 2022)
This study aimed to determine the prosocial behavior of elementary school high-grade students based on gender differences in society 5.0. Challenges in fostering students' prosocial behavior as barriers for teachers to pay attention to students, difficulties among teachers and parents in instilling prosocial behavior, students act against social behavior at school because they imitate the behavior of adults outside of school. The study used a quantitative approach with a descriptive method. The data measurement tool is a questionnaire in the form of a scale developed based on indicators of prosocial behavior. The research population was all high-class students at SDN Sentol Laok, Sumenep Regency, totaling 84 students. Based on the examination results, the prosocial behavior in students is helping, being generous, sharing, acting honestly, and working together. Students show this according to student practice both inside and outside the classroom. Efforts made by teachers in instilling prosocial behavior in students are generating, showing, enforcing rules and social activities. Inspiring is the main effort in instilling and fostering students' prosocial behavior. While students' prosocial behavior is included in the moderate category with an average value of 1.89, students can display and demonstrate their prosocial behavior. The results showed that male adolescents had higher prosocial behavior than female adolescents due to differences in physical and psychological factors such as effective differences, cognitive differences, parenting factors, and age.